Twelve Physical Education Teachers' Experiences towards COVID-19: A Look from Different Latin Contexts - Colindres Molina, Dilia (2022)
The COVID-19 emergency had an impact on life in the planet and brought with it a series of changes at the educational level, which exposed problems that already existed but became even more visible with the passage of this pandemic. Teachers around the world had to face this situation in order to allow continuity in the teaching-learning processes. For example, they resorted to various forms of training and investment in various tools to reach students, mainly virtual platforms and electronic devices. In this paper, the experiences of twelve teachers from seven Latin American countries are shared, showing an overview of Physical Education in times of COVID-19, experiences that have made it possible to identify advantages, disadvantages, opportunities and new challenges that are projected in a near future.